Hubungan Prokrastinasi, Budaya Ngaret dengan Agresivitas Berkendara di Wilayah Jabodetabek - Melodius Yusuf Hekmatyar; Johan Ramadhan Nurwardana (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The increasing number of motor vehicles, which has led to a rise in traffic congestion and accidents on the roads, has become a common phenomenon in major cities in Indonesia. This research aims to investigate the relationship between procrastination, known as "the culture of being late," and aggressive driving in the Jabodetabek area. Procrastination, or the habit of delaying, has become a common phenomenon in Indonesian society and is often associated with aggressive behavior on the roads. This research uses the General Procrastination Scale (GPS) and the Aggressive Driving Scale to measure the levels of procrastination and aggressive driving among a sample of adult drivers aged 17-35 years. The analysis results indicate a significant positive relationship between procrastination and aggressive driving, particularly in the Jabodetabek area, with a correlation coefficient (r) of 0.833, where individuals with a high tendency to procrastinate tend to be more aggressive while driving. This finding provides insights into how procrastination behavior can contribute to risky driving behavior, highlighting the importance of time management and self-control in the context of road safety.